Homem, animal, indústria: uma análise discursiva do agronegócio brasileiro - Alves Filho, Manoel Sebastião (2020)
This dissertation intends to analyze the discursive functioning of the Brazilian agribusiness in order to better understand a paradox of contemporary society: the excessive consumption of meat, the systematic killing of millions of animals, the commercial success of the meat industry in a society sensitive to animals. The work is divided into three units: the first makes a quick flight over history, looking for discourses produced by human beings about animals; the second analyzes society’s ambivalences regarding these living beings; the third analyzes the role of the industry in our country and the discourses produced by it, namely by Friboi, Seara, Sadia e Perdigão. Initially, we sought to say about the relationship of man with the animal in the long historical period, abstracting passages in which the first attributed characteristics such as sensitivity, emotion, conscience and language or insensitivity, ignorance and passivity, in order to determine its status and your right or not to life. We start from common discursive units, such as specific fields of knowledge, authors, works and periods, in search of the identification of more fundamental statements and discourses, whose strength and reach make them go beyond these fields, pass from one author to another, expand and cross the boundaries of time and space, of ages and places: animals have euphoric properties and we mustn’t kill and eat them or they do not and we can do it. Then, we analyze the ambiguities that permeate today's society in this regard: sensitivity to certain species; the practice of eating or not eating animal foods; the defense of better living conditions and a humane slaughter for industrial animals or the defense of the cessation of this entire carnivorous industrial system; the adoption of individual practices such as vegetarianism or veganism as a strategy for sabotage etc. Finally, we analyze national agribusiness speeches about their products and their production, observing the materialization of words that, through linguistic and imaginary resources such as metaphor and metonymy, produce certain effects of meaning that highlight the former and silence the latter, which they conceive of meat as a product and a food and not as the fragment of an individual animal, endowed with attributes such as sensitivity, emotion, conscience, etc. Our theoretical assumptions and analytical procedures come from the Discourse Analysis of the French line derived from Michel Pêcheux and Michel Foucault. Our material, in turn, comprises advertisements, website texts and packaging of the mentioned brands.